Harnessing the climate mitigation, conservation and poverty alleviation potential of seagrasses: prospects for developing blue carbon initiatives and payment for ecosystem service programmes - Hejnowicz, Adam P.; Kennedy, Hilary; Rudd, Murray A.; Huxham, Mark R. (Frontiers in Marine Science, 2015)
Seagrass ecosystems provide numerous ecosystem services that support coastal communities around the world. They sustain abundant marine life as well as commercial and artisanal fisheries, and help protect shorelines from coastal erosion. Additionally, seagrass meadows are a globally significant sink for carbon and represent a key ecosystem for combating climate change. However, seagrass habitats are suffering rapid global decline. Despite recognition of the importance of ‘Blue Carbon’, no functioning seagrass restoration or conservation projects supported by carbon finance currently operate, and the policies and frameworks to achieve this have not been developed. Yet, seagrass ecosystems could play a central role in addessing important international research questions regarding the natural mechanisms through which the ocean and the seabed can mitigate climate change, and how ecosystem structure links to service provision. The relative inattention that seagrass ecosystems have received represents both a serious oversight and a major missed opportunity. In this paper we review the prospects of further inclusion of seagrass ecosystems in climate policy frameworks, with a particular focus on carbon storage and sequestration, as well as the potential for developing payment for ecosystem service (PES) schemes that are complementary to carbon management. Prospects for the inclusion of seagrass Blue Carbon in regulatory compliance markets are currently limited; yet despite the risks the voluntary carbon sector offers the most immediately attractive avenue for the development of carbon credits. Given the array of ecosystem services seagrass ecosystems provide the most viable route to combat climate change, ensure seagrass conservation and improve livelihoods may be to complement any carbon payments with seagrass PES schemes based on the provision of additional ecosystem services.